2023
DOI: 10.1186/s12879-023-08533-0
|View full text |Cite
|
Sign up to set email alerts
|

The incidence rate of tuberculosis and its associated factors among HIV-positive persons in Sub-Saharan Africa: a systematic review and meta-analysis

Temesgen Gebeyehu Wondmeneh,
Ayal Tsegaye Mekonnen

Abstract: Background Tuberculosis, along with HIV, is the leading cause of mortality and morbidity globally. Despite the fact that several primary studies have been conducted on the incidence rate of tuberculosis in HIV-infected people in Sub-Saharan Africa, the regional-level tuberculosis incidence rate remains unknown. The objective of this study is to determine the tuberculosis incidence rate and its associated factors in HIV-infected people in Sub-Saharan Africa. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…The final report of this research indicated treatment failure experienced PLHIV who did not receive isoniazid preventive therapy (IPT) had a significant risk of active TB incidence after treatment failure experienced (AHR: 13.225, 95% CI: 2.894–60.434, p = 0.001). This is consistent with previous meta‐analysis findings in Ethiopia 15 , 18 and supported with premier studies. 38 , 39 , 40 This might be related to the concomitant IPT with ART administration reducing or demoted new cases of TB incidence and associated deaths by over 90% for PLHIV.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The final report of this research indicated treatment failure experienced PLHIV who did not receive isoniazid preventive therapy (IPT) had a significant risk of active TB incidence after treatment failure experienced (AHR: 13.225, 95% CI: 2.894–60.434, p = 0.001). This is consistent with previous meta‐analysis findings in Ethiopia 15 , 18 and supported with premier studies. 38 , 39 , 40 This might be related to the concomitant IPT with ART administration reducing or demoted new cases of TB incidence and associated deaths by over 90% for PLHIV.…”
Section: Discussionsupporting
confidence: 93%
“… 38 , 39 , 40 This might be related to the concomitant IPT with ART administration reducing or demoted new cases of TB incidence and associated deaths by over 90% for PLHIV. 15 However, factors like IRIS, inadequate active TB screening by a caregiver, low IPT completion of PLHIV, and poor comprehensive care during successive follow‐up shifts end positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study from the UK also showed that having a country of birth with a high tuberculosis burden was a significant risk factor for developing active HIV-related tuberculosis [ 18 ]. A meta-analysis among PLWH in Sub-Saharan Africa revealed that being underweight, having a low CD4 count, male gender, advanced WHO clinical stages, anemia, bedridden/ambulatory functional status, lack of isoniazid preventive therapy and lack of cotrimoxazole could boost the risk of tuberculosis occurrence [ 19 ].…”
Section: Epidemiology Of Hiv-related Tuberculosismentioning
confidence: 99%